Advanced computation methods for soil-structure interaction analysis of structures resting on soft soils. Issue 4 (4th July 2019) - Far, Harry
Abstract: Adopting the most accurate and realistic modelling technique and computation method for treatment of dynamic soil–structure interaction (SSI) effects in seismic analysis and design of structures resting on soft soil deposits is one of the most discussed and challenging issues in the field of seismic design and requalification of different structures. In this study, a comprehensive critical review has been carried out on available and well-known modelling techniques and computation methods for dynamic SSI analysis. Discussing and comparing the advantages and disadvantages of employing each method, in this study, the most precise and reliable modelling technique as well as computation method have been identified and proposed to be employed in studying dynamic SSI analysis of structures resting on soft soil deposits.